Sistem Pembelajaran Kolaborasi di MIS Muhammadiyah 4 Jetis Ponorogo - Satijah, Rezika Rahmalia; Putra Purnama, Ramadan; Rahmalia Shofa, Rezika; Dzaky Musyaffa, Riza; Mutiasari, Rizkya (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article aims to investigate collaborative learning systems to enhance active student engagement through interaction and cooperation. This is considered important because some learning systems are still detected, where classroom activation is still teacher-centered. The research examines various methods and strategies that support collaborative learning. Collaborative learning facilitates active learning where students work in groups to achieve common goals, share knowledge, and develop social and cognitive skills. This research used qualitative methods. The data obtained from this study used secondary data with a review of existing literature. To strengthen in data analysis, researchers used the interview method directly to one of the teachers at MIS Muhammadiyah 4 Jetis Ponorogo. The results of what we found showed that in the collaborative learning system at MIS Muhammadiyah 4 Jetis Ponorogo all students were actively involved in the learning process. The focus of this research is to find out whether the collaborative learning system can increase students' active involvement in the learning process.